Effects of low-frequency rTMS combined with speech and language therapy on Broca’s aphasia in subacute stroke patients - Gan, Li; Huang, Litao; Zhang, Yin; Yang, Xin; Li, Lijuan; Meng, Lijiao; Wei, Quan (Frontiers in Neurology, 2024)
Introduction Broca’s aphasia is a crushing syndrome after stroke. Although there are multiple therapies, the recovery of a considerable number of patients is still not ideal. Repetitive transcranial magnetic stimulation (rTMS) combined with speech and language therapy has been a promising combination regimen in recent years. However, the efficacy and persistent effects thereof remain unclear. We aimed to determine the immediate and long-term effects of rTMS combined with speech and language therapy on subacute stroke patients with Broca’s aphasia and explore relevant mechanisms in the picture-naming task via functional near-infrared spectroscopy (fNIRS). Materials and methods This was a prospective clinical study. In accordance with the inclusion criteria, 18 patients with post-stroke were recruited and randomly divided into either the rTMS group or the sham-rTMS group. Patients in both groups received low-frequency rTMS therapy for 20 min a day and then speech and language therapy for 30 min a day, 5 days a week, for a total of 4 weeks. Two groups of patients underwent the Western Aphasia Battery Revised (WAB-R), the Stroke and Aphasia Quality of Life Scale-39 (SAQOL-39), and non-language-based cognitive assessment (NLCA) before treatment and at 2 weeks, 4 weeks, and 3 months after treatment. Meanwhile, we collected fNIRS task state data while naming images before and after 4 weeks of treatment. The primary outcome was WAB-R changes. The secondary outcomes include the SAQOL-39, NLCA, as well as the difference in activation status of brain regions in the cortical language function network. Results For the index scores of the two groups, the results of repeated-measures ANOVA indicated an increasing trend at three time points, i.e., after 2 weeks of treatment, 4 weeks after treatment, and 3 months after the end of treatment (p < 0.001); in terms of intergroup effects, there was a statistically significant difference between the two groups in WAB naming scores (F = 4.865, p = 0.042); and the aphasia quotient (AQ), listening comprehension, and naming scores of the two groups had interactive effects (FAQ = 11.316, PAQ = 0.000; Flistening = 8.205, Plistening = 0.002; Fnaming = 27.46, Pnaming = 0.000). Independent sample t-tests also showed that until 4 weeks after the end of treatment, there were significant differences in information volume and naming scores between the two groups (tinformation = 2.352, Pinformation = 0.032; tnaming = 3.164, Pnaming = 0.006). Three months after the end of treatment, there were significant differences in information volume, naming, AQ and repetition scores (tinformation = 2.824, Pinformation = 0.012; tnaming = 5.090, Pnaming = 0.000; tAQ = 2.924, PAQ = 0.010; trepetition = 2.721, Prepetition = 0.015). In the picture-naming task, fNIRS analysis found that in the rTMS group after treatment, the activation in the left superior temporal gyrus (STG), middle temporal gyrus (MTG), premotor cortex (PM), supplementary motor area (SMA), pars triangularis Broca’s area, and dorsolateral prefrontal lobe (DLPFC) decreased (p < 0.05). Conclusion The language function of patients was improved after 4 weeks of treatment, and there was a long-term effect (3 months follow-up), especially in naming gains. Moreover, by analyzing cortical activation during a picture-naming task with fNIRS, we found that rTMS could downgrade the activation level in the left MTG, STG, PM and SMA, DLPFC, and pars triangularis Broca’s area, whereas the sham-rTMs group only showed downgraded activation levels in the right PM and SMA. This demonstrates the unique mechanism of rTMS. Clinical trial registration: ChiCTR.org.cn, identifier, ChiCTR2300067703.